Extended Reality (XR) Technologies That Threaten Democracy: Criticism of Virtual Reality Manipulation - Patrissia, Ressa Uli (International Journal of Social Service and Research, 2025)
This study aims to analyze how Extended Reality (XR) technology, as a product of modernity, threatens democracy by evaluating the role of digital gatekeepers in constructing reality and representational dominance. Employing a critical hermeneutics method within a critical communication paradigm, the research reveals that XR produces sensory experiences that diminish users’ reflective capacity toward shared reality. Findings indicate that XR is used to build hegemonic narratives through algorithmic personalization, leading to epistemic dissociation and the weakening of public deliberation. Nonetheless, user resistance is emerging, albeit limited. This research asserts that XR represents a new power arena in the digital ecosystem, demanding ethical regulation and critical digital literacy.